Identification of Phenotypic Diversity and DArTseq Loci Associated with Vitamin A Contents in Turkish Common Bean Germplasm Through GWAS - Yeter Çilesiz; Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Amjad Ali; Uğur Sesiz; Ahmad Alsaleh; Ahmet İlçim; Mehmet Sertaç Özer; Tunahan Erdem; Israr Aziz; Sheikh Mansoor; Tolga Karaköy; et al. (Plants)
Biofortification has emerged as an important approach for improving minerals and vitamin deficiencies through the application of agronomic and biotechnological methodologies. Vitamin A, one of the most deficient vitamins, disproportionately affects children in developing countries, highlighting the urgent need for vitamin A-enriched cultivars. The present study aimed to characterize common bean germplasm for vitamin A contents and to identify the genomic regions associated with this trait. A total of 177 common bean landraces and 6 commercial cultivars were evaluated under five environments and two locations. Analysis of variance revealed highly significant environmental effects and genotype × environment interactions. Across all years and all locations, Bilecik-6 exhibited the lowest vitamin A contents (1.67 µg/100 g dry seed), while Civril-Bolu had the highest (3.23 µg/100 g dry seed). Landraces from Balıkesir province were found to be rich in vitamin A content and should be considered as potential genetic resources for common bean biofortification. Additionally, a genomic region located on Pv06 was identified as being linked to vitamin A content. The genomic and genetic resources identified in this study will be valuable for the breeding community aiming to develop vitamin A-enriched common bean cultivars.